STEREOTIP MAKNA KEPERAWANAN (VIRGINITY) REMAJA PEREMPUAN DALAM MASYARAKAT PEDESAAN - Putri, Pratiwi Prasetyo (Martabat: Jurnal Perempuan dan Anak, 2019)
ABSTRACT. Virginity in the context of Indonesia still has high sacrality and is considered very important in society. It is different in the Western World which considers virginity not to be debated, even free sex has become a normal activity. In Indonesia, there are two sides to different cultures, namely the culture of urban communities and rural communities. Rural communities hold fast to traditions, morals and customs and uphold values ??and norms. Young women who lose their virginity with various factors will be considered as a violation and disgrace which is very embarrassing even to the point of being discarded by their family to be exiled by the community. In contrast to urban communities, although only some people consider loss of virginity to be an impact of association that can happen to anyone. On this basis researchers are interested in looking at the stereotypes of rural communities in the sense of virginity of female adolescents in Karanganyar Village, South Lampung Regency, to find the other side of discrimination is virgin girls. This research uses qualitative method with a population of 200 people in Karanganyar village, but the samples studied were 20 randomly selected people through observation and interview techniques. The results of this research are to find out the stereotypes of meaning that are built up about the virginity of female adolescents in rural communities to maintain culture and customs according to prevailing values ??and norms.